Evaluation of the effect of air pollution on cognitive functions, cognitive decline, and dementia - Fettah Eren; Serefnur Ozturk (Annals of Indian Academy of Neurology, 2022)
The incidence of dementia increases with aging. It is known that the disease brings with it many problems for patients and caregivers. Studies on the development of various treatment modalities for the disease continue. However, the main step in the management of this process is the identification of dementia risk factors. The prevalence of dementia is higher in those living in urban areas where exposure to air pollution and chemical effects is higher. This situation supports the relationship of air pollution, which has increased especially in the last decade, with the increase in cognitive decline and dementia frequency. Exposure to air pollution is one of the well-known causes of neurological diseases. This condition was associated with significant disability and early mortality. Although the close relationship between cerebrovascular diseases and air pollution is known, current studies also reveal the relationship between neuropsychiatric diseases and air pollution. It has been shown that microparticles inhaled through the respiratory system are responsible for this situation. Although individual sensitivity is prominent in the disease, the etiopathogenetic process remains relatively uncertain. Researchers have detected that the relationship between dementia and air pollution is because of the effects of increased proinflammatory mediators and reactive oxygen radicals. Evaluation of air pollution, which plays a role in the etiopathogenesis of dementia, in the light of current literature and revealing this relationship will provide important contributions in taking the necessary measures to prevent the disease.